The Relationship Between Maternal Characteristics And Folic Acid Intake With The Incidence Of Anemia In Pregnant Women In Percut Sei Tuan Sub-District - Mahdiah Mahdiah; Atika Salma Rahmadani (Jurnal Health Sains, 2023)
Background: Anemia is one of the nutritional problems with a high prevalence. Anemia often occurs in adolescents, women of childbearing age, and pregnant women. Objective: to determine the relationship between maternal characteristics and folic acid intake with the incidence of anemia in pregnant women Method: the design of this study is Cross Sectional. The population is all pregnant women in the second and third trimesters in three villages of Percut Sei Tuan sub-district. Sampling in this study was porpusive sampling. Data collection was conducted by interviews using questionnaires and food recall tables as research instruments. Data processing through editing, entering and tabulating. Data analysis using Chi Square test with Ci 95% Results: the results showed that mothers with a good age group did not experience anemia as much as 87.5% and mothers with a bad age group experienced anemia as much as 15.5%. Mothers with good parity group were not anemic as much as 96.9% and mothers with poor parity anemia were 37.5%. Mothers with good ANC group had anemia as much as 96.9% and mothers with ANC group not good did not experience anemia 37.5%. Pregnant women with good folic acid intake group were not anemic as much as 54.5% and mothers with poor folic acid group were anemic as much as 87.5% Conclusion: There is a relationship between parity, ANC visits and folic acid intake in pregnant women in Percut Sei Tuan District. And there is no relationship between maternal age and the incidence of anemia in Percut Sei Tuan sub-district